Physical versus augmented reality model: Comparative study toward learning experiences at heritage studies gallery - Kassim, Mohd Hisyammudin; Abdullah, Fadzidah; Denan, Zuraini; Ahmad Arafat, Khandoker (American Scientific Publisher, 2017)
The research focuses on the comparison of students’ perception toward learning experience between the usage of physical models and Augmented Reality (AR) models of architectural heritage at Heritage Studies Gallery. Currently, the gallery has embedded Mobile Augmented Reality (MAR) technologies as an alternative in collecting, preserving and displaying the collection. It is anticipated that AR models is preferable as compared to physical models in the context of the gallery display for learning experience. However, architectural education still believed in physical models as a medium of communication that assist students’ learning experiences. In this research, the AR models are not going to replace the roles of physical models, but they are used to assist students’ learning by utilising 3D visualizing media especially for architectural heritage education. Thus, the objectives of this research are to highlight the role of both media in architectural heritage education and to compare the students’ perceptions of their learning experience between utilising physical models versus using AR models of Architectural Heritage. The research applied qualitative-quantitative mixed research approach, where the observation through video cameras and questionnaires are used to obtain primary data. The video observation and questionnaire on the students’ perception would be collected right after the students experience the learning process at the gallery. The reflection highlights the role of both media toward the students learning experience especially in architectural heritage education at the gallery. The research also looking forward on collaborative learning by combining both media which could be applied to other disciplines.